PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TEHADAP KEPUTUSAN PEMBELIAN PRODUK NISSIN BISKUIT (STUDI KASUS PADA NISSIN CAFE EMPORIUM - Setiawan, Pulung; Waloejo, Handoyo Djoko (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2019)
The food and beverage industry as part of the FMCG industry (Fast Moved Consumable Goods) is one of the industries that experienced significant growth from year to year. shows that the growth trend of the domestic food and beverage industry is quite good One of the many industries included in the food and beverage industry is the biscuit industry. The strategies that can be taken are product quality, price and brand image so that it can encourage the increase of Nissin Biscuit purchasing decisions.Â The purpose of this study was to determine the effect of product quality, price and brand image on purchasing decisions of Nissin Biscuit product case studies at Nissin Cafe Emporium. The type of research used is explanatory research. The sampling technique uses a non-probability sampling method, the respondents used in this study were consumers of Nissin Cafe Emporium. Respondents in this study amounted to 100 respondents. Processing data using questionnaires with a linkert scale. Validity test, reliability test, cross tabulation, correlation coefficient, coefficient of determination, simple and multiple regression analysis, significance test (t test and F test). by using SPSS program assistance.Â The results showed that all variables in this study had a positive and significant influence on the dependent variable. This is indicated by the results of the multiple correlation coefficient test of 0.809. Significantly, the product quality, price and brand image variables have a positive effect, indicated by the calculated F value greater than F table which is equal to 60.799> 2.70. The advice that can be given is that Nissin Biscuit should be able to continue to provide better quality or quality in the future, increasing the attractiveness of consumers in consuming and enhancing the impression that Nissin Biscuit is worth buying